The Role of Information Technology in Instilling Akhlaqul Karimah in Elementary and Islamic Elementary School Students: A Conceptual Review - M. Zainal Mustamiin (Journal of Islamic Religious Studies, 2025)
In the digital era, Islamic education faces both opportunities and challenges in fostering Akhlaqul Karimah (noble character) among elementary students. The increasing exposure to digital content necessitates a strategic integration of information technology (IT) to reinforce moral and spiritual development. This conceptual review aims to examine the current practices of IT integration in Islamic character education, identify associated challenges and opportunities, and propose a conceptual framework to guide future practice. Using a qualitative conceptual review design, this study analyzed 20 peer-reviewed journal articles and scholarly books published within the last decade. Data were collected using a literature review matrix and analyzed through data reduction, display, and conclusion drawing, following the model of Miles, Huberman, and Saldaña. The results indicate that digital tools such as mobile applications, digital storytelling, Islamic multimedia, and e-books are widely utilized to support character education. These tools enhance engagement and provide innovative moral learning experiences. However, challenges such as limited digital literacy among teachers and insufficient infrastructure remain significant barriers. Despite this, the integration of IT offers promising opportunities to personalize learning, expand access to Islamic content, and gamify moral instruction. This study proposes a conceptual framework that bridges Islamic pedagogy with digital innovation, highlighting the pivotal role of educators in guiding ethical technology use. The findings provide theoretical insights and practical directions for curriculum designers, educators, and policymakers seeking to align digital transformation with Islamic moral values.